Firm resources and capabilities in omnichannel retailing - Sipinen, Jaana (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku. Turku School of Economics|, 2017)
During the past few years, the global retail industry has been under heavy disruption mainly due to prolonged economic slowdown, weakened consumer purchasing power and digitalization. Traditional retailers are facing more and more challenges in remaining profitable and sustaining their competitive advantage, which has called for more efficient use of their resources. New business models have emerged, and several scholars have stated that an omnichannel business model will be the most profitable business strategy in the future of retailing. This thesis aims to provide more information and deeper understanding on the concurrent retail business environment, focusing on examining what kind of firm resources and capabilities are considered essential in omnichannel retailing to create customer value and improve operations. Key concepts and theories related to firm resources, capabilities and omnichannel retailing are discussed in the literature review, which serves as a basis for a theoretical framework for the study. The existing knowledge of omnichannel retailing is assessed in the context of the Finnish retail industry. This study has adopted a qualitative case study approach, and five thematic semi-structured interviews were conducted among five top executives working for major Finnish retailers: Kesko Group, S Group and Stockmann. Thematic coding was used to analyze the empirical data. The findings of this research suggest that omnichannel retailing has become a fundamental element of the business strategies of major traditional Finnish retailers, and it is largely seen as the key driver for gaining competitive advantage. First, organizational transformation is regarded necessary, which includes among others, adopting new leadership styles, forming a lighter organizational structure, empowering teams and starting a cultural change. The second enabler of omnichannel retailing relates to adopting a heavy customer focus. To a growing extent, customer value is believed to be created by utilizing big data, identifying customer journeys and building digital services to support brick and mortar business. The essential firm resources and capabilities hence relate to managerial capabilities to drive organizational change and the managers’ ability lead with knowledge and data, in addition to acquiring any needed technical and analytical skills and technologies in to the organization.